Ultrahigh speed spectral-domain optical coherence microscopy - Lee, Hsiang-Chieh (Optical Society of America, 2013)
We demonstrate a compact, ultrahigh speed spectral-domain optical coherence microscopy (SD-OCM) system for multiscale imaging of specimens at 840 nm. Using a high speed 512-pixel line scan camera, an imaging speed of 210,000 A-scans per second was demonstrated. Interchangeable water immersion objectives with magnifications of 10×, 20×, and 40× provided co-registered en face cellular-resolution imaging over several size scales. Volumetric OCM data sets and en face OCM images were demonstrated on both normal and pathological human colon and kidney specimens ex vivo with an axial resolution of ~4.2 µm, and transverse resolutions of ~2.9 µm (10×), ~1.7 µm (20×), and ~1.1 µm (40×) in tissue. In addition, en face OCM images acquired with high numerical aperture over an extended field-of-view (FOV) were demonstrated using image mosaicking. Comparison between en face OCM images among different transverse and axial resolutions was demonstrated, which promises to help the design and evaluation of imaging performance of Fourier domain OCM systems at different resolution regimes.